2018
DOI: 10.1089/cap.2016.0183
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties and Factor Structures of the Korean Version of Children's Depression Rating Scale-Revised

Abstract: This study of the Korean version of the CDRS-R provides initial promising data regarding its criterion validity, discriminant validity, internal consistency, and factor structures. These properties were significantly strong, which suggests that the Korean version of the CDRS-R is a valid and reliable instrument for the assessment of depressive symptoms in youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 30 publications
5
33
0
Order By: Relevance
“…It includes 17 symptoms-related items, derived from the adult Hamilton Depression Rating Scale, which are rated by clinical interviewers based on the summary of child and parent reports and their behavioral observation during the interview. Excellent internal consistency of the Korean version of the CDRS-R was reported (Cronbach's α = 0.91) 44 . This scale had good internal consistency in this sample (Cronbach's α = 0.93).…”
Section: Clinical Assessments and Self-report Measures The Participamentioning
confidence: 95%
“…It includes 17 symptoms-related items, derived from the adult Hamilton Depression Rating Scale, which are rated by clinical interviewers based on the summary of child and parent reports and their behavioral observation during the interview. Excellent internal consistency of the Korean version of the CDRS-R was reported (Cronbach's α = 0.91) 44 . This scale had good internal consistency in this sample (Cronbach's α = 0.93).…”
Section: Clinical Assessments and Self-report Measures The Participamentioning
confidence: 95%
“…18 As no acceptable "gold-standard" for quantifying depression symptom severity in adolescents was identified by the review team, criterion validity was not considered evaluable for the CDRS-R, and as recommended, 18 the single study that reported evaluating "criterion validity" was included as an evaluation of construct validity. 27 Three reviewers (ES, SM, MO) independently recorded which of these nine measurement properties each study assessed according to COSMIN's measurement properties definitions.…”
Section: Measurement Propertiesmentioning
confidence: 99%
“…These three items are rated based on the interviewer's observation only. In this study, we used the Korean version of the CDRS-R, which showed high internal consistency (a = 0.91) and strong criterion and discriminant validity (Kim et al 2017). A total score of 40 or higher on the Korean version of the CDRS-R indicates the presence of depressive disorder.…”
Section: Symptom Measuresmentioning
confidence: 99%